The Diagnostic Superiority of the HE-4 Marker over CA-125 and CA 19-9 in the Differentiation of a Large Pelvic Tumor – a Case Report. Issue 1 (January 2013) - Chudecka-Głaz, Anita; Menkiszak, Janusz; Cymbaluk-Płoska, Aneta; Rutkowski, Donald; Kawa, Miłosz; Wilk, Grażyna
The HE-4 protein is a promising specific marker for the diagnosis of malignant pelvic tumors. The paper presents the case of a 41-year-old patient with a multi-chamber ovarian tumor several centimeters in diameter suspected to be a primary ovarian cancer or a metastatic one of gastrointestinal origin. The value of the HE-4 marker which is highly specific for an ovarian cancer was within normal limits and amounted to 24.33 pmol/L. The patient underwent surgery involving the unilateral removal of adnexa and the greater omentum during which the sample from the second ovary was collected. Histologic examination revealed ovarian endometriosis; however, diagnosis of the gastrointestinal tract did not reveal any abnormalities. The case presented also confirms the excellent sensitivity of the HE-4 marker in very difficult clinical cases, as well as its utility in the differential diagnosis of advanced endometriosis and malignant ovarian diseases.